Human resource planning and service readiness: Health workforce intervention at Tora Belo Regional Hospital - Afrilianto, Muhammad Barkah; Napirah, Muhammad Ryman; Miranti, Miranti (Sociality: Journal of Public Health Service, 2025)
Human resource management (HRM) planning is a key health system intervention to ensure service readiness, quality of care, and workforce sustainability, particularly in rural hospital settings. However, empirical evidence examining how HRM planning is implemented at the district hospital level remains limited. This study aims to analyze human resource planning at Tora Belo Regional General Hospital, Sigi Regency, as a facility-level intervention supporting effective health service delivery. A qualitative case study approach was conducted from July to August 2025. Data were collected through in-depth interviews, observation, and document review involving three purposively selected informants: the Hospital Director, Head of Administration, and hospital officers. Data were analyzed using systematic stages of data collection, reduction, presentation, conclusion drawing, and verification, supported by technical and source triangulation. The findings show that major components of human resource planning—procurement, development, compensation, maintenance, discipline, and termination—have generally been implemented well and contribute to workforce stability and continuity of services. Nevertheless, limitations remain in the absence of workload-based analysis and standardized competency frameworks, which restrict responsiveness to evolving service demands. This study highlights the importance of strengthening HRM planning as a strategic health intervention through the integration of human resource workload analysis, competency-based recruitment, and improved coordination between planning, budgeting, and service delivery. These measures are essential to support accurate, equitable, and sustainable workforce formation and to enhance the performance of rural hospitals.